Manajemen Queue Layanan Kesehatan: Pemanggilan Pasien Otomatis Berbasis IoT–Fasilitas Perawatan Primer - Abi Ari Sandy; Septriandi; Zanu Saputra; Yus Dwi Santi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2025)
Community Health Centres (Puskesmas) as primary health care facilities face problems in queue management that affect service satisfaction and efficiency. Manual queuing systems, which are still commonly used, cause patient backlogs, irregular queuing, and psychological stress, especially for vulnerable groups such as the elderly and children. This study aims to design and implement an Internet of Things (IoT)-based automatic queue calling system to improve service effectiveness at Puskesmas. The methods used include case studies, field observations, and comprehensive system testing. This system integrates an ESP32 microcontroller as the control centre with various supporting components, including a thermal printer for printing queue tickets, a DFPlayer Mini module with a speaker for audio notifications, a P10 LED panel for visual display, and a 20x4 LCD with RTC for real-time monitoring. The system is also connected to a web platform via Firebase for recording and monitoring queue data. Test results show that the system operates optimally in all aspects, with clear audio output up to a distance of 15 metres, a printer that can print tickets consistently, and a clear visual display on the P10 panel. This system has proven effective in reducing patient waiting times, improving service comfort, and assisting staff in managing queues efficiently. The implementation of IoT technology in the queue calling system has made a significant contribution to improving the quality of public health services in the digital era